1990
DOI: 10.1063/1.346529
|View full text |Cite
|
Sign up to set email alerts
|

A thermally activated solid state reaction process for fabricating ohmic contacts to semiconducting diamond

Abstract: Techniques have been developed to produce ohmic contacts to naturally occurring boron doped semiconducting diamond. Thin films of Mo, Mo/Au, and Mo/Ni/Au deposited on diamond produced adherent ohmic contacts after annealing at 950 °C. A thermally activated solid state reaction which produces a refractory carbide precipitate at the original diamond/metal interface is the principal factor in affecting the properties of the contacts. The interface reaction has been characterized using Auger electron spectroscopy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
4

Year Published

1996
1996
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(17 citation statements)
references
References 31 publications
1
12
0
4
Order By: Relevance
“…The low contact resistivity has been traced back to the formation of SiC at the metal±diamond interface. Similar results were reported for carbide forming metals like Ti [66] and Mo [67]. Tachibana et al [66] suggested two models which may explain the drop in the contact resistance or the change in the current±voltage characteristic from rectifying to ohmic.…”
Section: Ohmic Contacts To Diamondsupporting
confidence: 73%
“…The low contact resistivity has been traced back to the formation of SiC at the metal±diamond interface. Similar results were reported for carbide forming metals like Ti [66] and Mo [67]. Tachibana et al [66] suggested two models which may explain the drop in the contact resistance or the change in the current±voltage characteristic from rectifying to ohmic.…”
Section: Ohmic Contacts To Diamondsupporting
confidence: 73%
“…One can expect the same advantages when using carbides to contact carbon-based semiconductors. While titanium has already been used to contact diamond 5,6 and CNTs, 7 relatively little work has been reported concerning carbide formation during thin film reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Titanium, which has a great of affinity for carbon, was used by several groups of researchers to obtain ohmic contacts with diamond. 6,7 The Schottky barrier height would decrease greatly due to the formation of titanium carbide. As for our samples, this ohmic behaviour might be due to TiC formation upon sputter deposition of the titanium overlayer.…”
Section: Electrical Propertiesmentioning
confidence: 99%